A Mediation Role of Organizational of Learning on Relationship of Hard Skills, Soft Skills, Innovation and Performance: Evidence at Islamic School - Muhamad Agung Ali Fikri; Masduki Asbari; Agus Purwanto; Yunianto Agung Nugroho; Hatoli Waruwu; Ahmad Fauji; Abdul Wahid Imam Shobihi; Eman Singgih; Rachma Nadhila Sudiyono; Eva Agistiawati; Wulan Rahma Dewi (Universitas Muhammadiyah Enrekang, 2020)
The purpose of this research was to measure the effect of hard skills and soft skills towards teachers’ innovation capability in Jakarta, Bogor, Depok, Tangerang and Bekasi (Jabodetabek) which was mediated by an organizational learning and to measure the effect of teachers’ innovation capability towards their performance. Data collection was done by simple random sampling via electronic to the teacher population in Jabodetabek. The returned and valid questionnaire results were 676 samples. Data processing was used SEM method with SmartPLS 3.0 software. The results of this research concluded that hard skills and soft skills have a positive and significant effect on the capability of teachers’ innovation, both directly and indirectly through mediation of the organizational learning. As well as the capability of teachers’ innovation has a positive and significant effect on their performance. This new research proposed a model for building innovation capability and teachers’ performance among teachers in Jabodetabek through enhancing hard skills and soft skills with the organizational learning as a mediator. This research can pave the way to improve teachers’ readiness in facing the education era 4.0.